2021
DOI: 10.1002/ctm2.267
|View full text |Cite
|
Sign up to set email alerts
|

Serum and urinary biomarkers of collagen type‐I turnover predict prognosis in patients with heart failure

Abstract: Serum and urinary biomarkers of collagen type-I turnover predict prognosis in patients with heart failure Dear Editor, Previous studies indicated an association of biomarkers reflecting collagen turnover with heart failure. 1,2 However, their value in predicting unfavorable outcomes is unknown. In the myocardium, the collagen matrix forms a scaffold that maintains the anatomical integrity and function of the heart. Collagen I is dominant among the four primary types of cardiac collagen. 3 The abundance of coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
3
6
0
Order By: Relevance
“…When investigating the distribution of the few highly negatively (rho < −0.3) correlated significant peptides, it appears that the first and last peptides, that show such an inverse association with eGFR, originate from the N-and C-termini of the mature col1a1, respectively. This observation is similar to an observation recently reported by He et al [10], where the authors found an increase of N-and C-terminal collagen type I fragments associated with death in the context of heart failure, while the peptides from the central part of collagen type I that were significantly associated with death in this prospective study were all reduced. Based on these data, the hypothesis was presented that increasing cross-linking over time as a result of chemical modification due to ageing, inflammation or diabetes renders collagen fibers more resistant to degradation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When investigating the distribution of the few highly negatively (rho < −0.3) correlated significant peptides, it appears that the first and last peptides, that show such an inverse association with eGFR, originate from the N-and C-termini of the mature col1a1, respectively. This observation is similar to an observation recently reported by He et al [10], where the authors found an increase of N-and C-terminal collagen type I fragments associated with death in the context of heart failure, while the peptides from the central part of collagen type I that were significantly associated with death in this prospective study were all reduced. Based on these data, the hypothesis was presented that increasing cross-linking over time as a result of chemical modification due to ageing, inflammation or diabetes renders collagen fibers more resistant to degradation.…”
Section: Discussionsupporting
confidence: 93%
“…For example, in a fibrosis-focusing study, two specific col1a1 peptides, among other collagen fragments, demonstrated a negative correlation with the degree of fibrosis [9]. This is in agreement with the observation that the downregulation of the col1a1 degradation process appears to be associated with progression of fibrosis in heart failure [10]. In the context of obesity-related nephropathy, col1a1 fragments were also among the most significant peptides correlating (negatively) to body mass index (BMI) and (positively) to estimated glomerular filtration rate (eGFR) [11].…”
Section: Introductionsupporting
confidence: 83%
“…However, in a recent study the value of urinary collagen type I peptides in predicting outcome in HF has been demonstrated. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, associations between urinary markers and clinical outcomes were not investigated. However, in a recent study the value of urinary collagen type I peptides in predicting outcome in HF has been demonstrated 32 …”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the role of each of these molecules warrants comprehensive and thorough investigation, because they are heavily involved in the pathogenesis of myocardial fibrosis and are related to arrhythmogenesis [69,70]. Although numerous clinical trials have been performed in the last two decades to evaluate the utility of these molecules as diagnostic or prognostic biomarkers in patients with HF, collagen turnover biomarkers and bone-related proteins have been found to be closely associated with all-cause and CV mortality and HF hospital admission [71,72]. These markers are not highly specific for detecting adverse cardiac remodeling, and abnormal concentrations have often been found in acute and stable coronary artery disease, valvular heart disease, cardiac hypertrophy, and cardiomyopathy (Table 3).…”
Section: Biomarkers Of Extracellular Matrix Remodelingmentioning
confidence: 99%